2021
DOI: 10.53555/nnssh.v7i10.1072
|View full text |Cite
|
Sign up to set email alerts
|

Diplomacy Promotion and Economic Development in Rwanda A Case of United States Embassy Kigali

Abstract: The Diplomacy performs a key role in shaping what takes area in international relations including bilateral relations, development aids, foreign policy and political and state interests. Diplomacy promotion is changing along with at least three dimensions, so the first is that in today’s world household participants work nationally to meet famous challenges. Not long ago, diplomacy used to promote hobbies throughout the country, while development used to be once the eradication of poverty. The intentions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…The results of the statistical analysis indicate that the p-value, which is below the threshold of 0.05, indicates a significant difference in leadership strategies and the impact of social welfare diplomacy on the promotion of sustainable economic growth in Nigeria and Rwanda. The findings presented in this study are in contrast to the research conducted by Uwera and Munene (2021), which did not identify a statistically significant association between the economic aspect of social welfare diplomacy and economic development. To eliminate the deficit in pension systems as an indicator for social welfare, restore their short-term viability, and ensure the long-term financing of a minimum level of old-age social insurance in a context of demographic ageing, Omrani, Chegrani, and Tahri (2023) concluded that countries must align to the reform measures recommended by international monetary authorities.…”
Section: Sustainable Economic Development Between Nigeria and Rwandacontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the statistical analysis indicate that the p-value, which is below the threshold of 0.05, indicates a significant difference in leadership strategies and the impact of social welfare diplomacy on the promotion of sustainable economic growth in Nigeria and Rwanda. The findings presented in this study are in contrast to the research conducted by Uwera and Munene (2021), which did not identify a statistically significant association between the economic aspect of social welfare diplomacy and economic development. To eliminate the deficit in pension systems as an indicator for social welfare, restore their short-term viability, and ensure the long-term financing of a minimum level of old-age social insurance in a context of demographic ageing, Omrani, Chegrani, and Tahri (2023) concluded that countries must align to the reform measures recommended by international monetary authorities.…”
Section: Sustainable Economic Development Between Nigeria and Rwandacontrasting
confidence: 99%
“…This finding highlights the significance of capacity building in promoting sustainable economic growth. According to the research conducted by Uwera and Munene (2021), capacity building diplomacy has been identified as a significant factor in the advancement of good governance and the facilitation of sustainable economic development. However, it is worth noting that, there are some aspects within this domain that might be enhanced for greater effectiveness.…”
Section: Methodsmentioning
confidence: 99%